Vacuum ultraviolet photoabsorption spectroscopy of crystalline and amorphous benzene. Issue 40 (5th October 2017) - Dawes, Anita; Pascual, Natalia; Hoffmann, Søren V.; Jones, Nykola C.; Mason, Nigel J.
Abstract : Vacuum ultraviolet spectra of amorphous benzene reveal significant shifts in electronic transitions and thickness dependent scattering during film growth. Abstract : We present the first high resolution vacuum ultraviolet photoabsorption study of amorphous benzene with comparisons to annealed crystalline benzene and the gas phase. Vapour deposited benzene layers were grown at 25 K and annealed to 90 K under conditions pertinent to interstellar icy dust grains and icy planetary bodies in our solar system. Three singlet–singlet electronic transitions in solid benzene correspond to the 1 B2u, 1 B1u and 1 E1u states, redshifted by 0.05, 0.25 and 0.51 eV respectively with respect to the gas phase. The symmetry forbidden 1 B2u ← 1 A1g and 1 B1u ← 1 A1g transitions exhibit vibronic structure due to vibronic coupling and intensity borrowing from the allowed 1 E1u ← 1 A1g transition. Additionally the 1 B2u ← 1 A1g structure shows evidence of coupling between intramolecular vibrational and intermolecular lattice modes in crystalline benzene with Davydov crystal field splitting observed. The optically forbidden 0–0 electronic origin is clearly visible as a doublet at 4.69/4.70 eV in the crystalline solid and as a weak broadened feature at 4.67 eV in amorphous benzene. In the case of the 1 B1u ← 1 A1g transition the forbidden 0–0 electronic origin is only observed in crystalline benzene as an exciton peak at 5.77 eV. Thicker amorphous benzene samples show diffuse bands around 4.3, 5.0 and 5.4 eV that we tentatively assign to spin forbidden singlet–triplet 3 B2u ← 1 A1g, 3 E1u ← 1 A1g and 3 B1u ← 1 A1g transitions respectively, not previously reported in photoabsorption spectra of amorphous benzene. Furthermore, our results show clear evidence of non-wetting or 'islanding' of amorphous benzene, characterised by thickness-dependent Rayleigh scattering tails at wavelengths greater than 220 nm. These results have significant implications for our understanding of the physical and chemical properties and processes in astrochemical ices and highlight the importance of VUV spectroscopy.